2016
DOI: 10.1016/j.jpurol.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Do adult men with untreated ventral penile curvature have adverse outcomes?

Abstract: Summary Introduction Congenital ventral penile curvature without hypospadias is often treated surgically in childhood. The history of untreated ventral curvature is unknown. Objective This study’s aim was to examine the association of untreated ventral penile curvature with various sexual and psychosexual outcomes. Study design An electronic survey was advertised to men older than 18 years on Facebook. Men with possible ventral penile curvature identified themselves by choosing sketches that most closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Ventral penile curvature associated with Hypospadias have more difficulty in intercourse, psychological issues because of penile appearance and maintaining straight flow of urine at the time of urination, besides having psychosocial issues. 13 Prevalence of 0.34% in this study is in sync with many studies.…”
Section: Discussionsupporting
confidence: 89%
“…Ventral penile curvature associated with Hypospadias have more difficulty in intercourse, psychological issues because of penile appearance and maintaining straight flow of urine at the time of urination, besides having psychosocial issues. 13 Prevalence of 0.34% in this study is in sync with many studies.…”
Section: Discussionsupporting
confidence: 89%
“…found an increased rate of recurrent penile curvature following dorsal plication when compared with corporal grafting (28% vs. 9%, p=0.03) 44 . Severe chordee, defined as penile curvature greater than 30 degrees, can be debilitating from both a urinary and a sexual function standpoint when it persists or recurs after primary repair 45 . Residual chordee occurs when the corrective procedure inadequately addressed the curvature at the initial procedure, while recurrent curvature appears because of disproportional corporal growth and may worsen as these boys progress through the exponential penile growth phase of puberty 44 , 46 .…”
Section: Factors Contributing To a High Complication Ratementioning
confidence: 99%
“…Emerging evidence has demonstrated that increases in the expression of genes associated with inflammatory disease coincide with expansion of Proteobacteria blooms ( Miyasaka et al, 2013 ; Mizuta et al, 2016 ; Nagao-Kitamoto et al, 2016 ). For example, the genus Pseudomonas (which belongs to the phylum Proteobacteria) has been frequently found to be correlated with infections ( Micek et al, 2005 ; Pobiega et al, 2016 ; Boutin et al, 2017 ). In our study, the bacterial order Pseudomonadales and genus Pseudomonas (which both belong to the phylum Proteobacteria) were distinguishing markers for PostD specimens.…”
Section: Discussionmentioning
confidence: 99%